CRFM LIB: uma ferramenta para aplicações com realidade aumentada - Moraes, Gilseone Rosa de (2018)
Augmented Reality (AR) is characterized by the addition of virtual elements to real-world images, creating a visual perception of interaction between virtual elements and real objects into a visual scene. Augmented Reality applications are developed to present interactive forms of visualization. Research using AR covers the most diverse areas, such as medicine, education, design, industrial maintenance, entertainment, architecture, among others. In order to further popularize applications that use this technological concept, increasingly accessible tools are needed in order to help developers build interactive experiences, using common technology resources such as smartphones or webcams. This dissertation presents the development of a tool for developing Augmented Reality applications for the Unity Game Engine, using as a reference target, the Colored and Recursive Fiducial Marker (CRFM). In the course of this work, the tools functionalities are described, encompassing processes such as Markers Generation, Color Matching, and also markers detections and projection of three-dimensional elements. In addition, it is presented the tools performance in relation to the CRFM markers detection, and how the use of the Color Matching process can aid detection when different types of lighting are applied.